Analisis Niat Beli Produk Glad2glow Melalui Platform Tiktok Menggunakan Modifikasi Information Adoption Model (IAM) - Firnanda Eka Kurniari; Dihin Septyanto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The development of social media has changed the way of marketing from traditional to digital, so the information received and adopted by consumers plays an important role in influencing their purchase decisions. This study aims to analyze the influence of information circulating on social media on purchase intention using Information Adaption Model (IAM) variables such as information quality, information credibility, quantity of information, information needs, information usefulness and information adoption. The method used in this study is quantitative descriptive to determine the cause and effect relationship of IAM variables on purchase intent. The population in this study is TikTok users who know Glad2Glow products in the Tangerang Regency area. The sampling technique used is non- probability sampling with the method is purposive sampling. The data analysis technique used is Partial Least Square-Structural Equation Modeling (PLS-SEM). The results of data processing show that the quality of information, credibility of information, quantity of information and information needs have a positive and significant effect on the usefulness of information. The usefulness of information has a positive and significant effect on information adoption and purchase intent. And the adoption of information positively affects purchase intent. This research contributes to companies to design more effective marketing strategies and increase the influence of information in shaping consumer purchase intentions. Future research is expected to use a larger scale of respondents and use different Platforms.